Characterization of stress-strain state in gas turbine engine compressor disc taking into account damage accumulation (Fracture and Structural Integrity, 2019)
The stress-strain state analysis of the gas turbine engine compressor disk was carried out taking into account damage accumulation under various loading conditions in the temperature range.Characterization of the constraint effects was performed using the local stress triaxiality h, TZ–factor and In-factors for the various crack sizes and different operation conditions.The distributions of elastic, plastic and creep stress intensity factors were determined by numerical calculation. The results were obtained for several crack front positions, temperature values and disk rotation angular velocity.The differences in the behavior of elastic and nonlinear fracture resistance parameters depending on loading conditions, crack geometry and temperature are demonstrated. The nonlinear stress intensity factors are preferred as fracture resistance parameters of materials and structures.
Keywords: Compressor disc; Damage; Surface flaw; Plastic stress intensity factor; Creep stress intensity factor